(untitled) (Asian Journal of Pharmaceutics (AJP), 2025)
Introduction: In Saudi Arabia, resin fumes have traditionally been used for home fragrance. Sandstorms pose health risks due to dust-borne fungal allergens; our study is to investigate the effectiveness of these fumes against such allergens. Objective: This study examined the efficacy of commonly used resin fumes, including oud, myrrh, and benzoin, against fungal allergens isolated from sandstorm dust in Zulfi, Saudi Arabia. Materials and Methods: Resin fumes (5 g) were generated using charcoal cake and introduced into a bell jar chamber containing pre-inoculated plates of sandstorm fungal isolates, including hyaline fungi (Penicillium spp., Fusarium spp., Aspergillus niger) and dematiaceous fungi (Ulocladium spp., Bipolaris spp., Cladosporium spp.). Control plates received no fume exposure. Fungal colonies were counted after 3–5 days of incubation and analyzed for log reduction. Results: Myrrh fumes demonstrated balanced efficacy against both hyaline (98.18% reduction) and dematiaceous fungi (84.3%). Oud fumes exhibited superior effectiveness against hyaline fungi (98.52%) but lesser activity against dematiaceous fungi (64.2%). Benzoin fumes showed moderate effectiveness against both fungal types. Synthetic incense cones resulted in a 100% reduction of fungal growth due to toxicity toward both types of fungi. Conclusion: This first report demonstrated the antifungal properties of traditionally used resin fumes, with myrrh fumes showing superior efficacy against both hyaline and dematiaceous fungi. The research identifies potential health risks from synthetic incense cones and highlights the lack of scientific studies on fume exposure for fungal control.